Compostos orgânicos voláteis de soro de leite no controle de Meloidogyne incognita - Silva, Maysa Siqueira Gonçalves da (2020)
The efficacy of agro-industry discards in controlling phytomatomatoids has been proven. An example is whey, which consists of a disposal of dairy products. As this control operates in the field, it has not yet been fully understood, much less the role of volatile compounds in toxicity. In the present study, whey emissions caused high immobility to juveniles of the second stage (J2) of Meloidogyne incognita. In them were identified by gas chromatography coupled with mass spectrometry (GC-MS) 27 molecules belonging to the chemical groups: ester; alcohol and carboxylic acid. Among them, four were selected for efficiency tests against eggs and M. incognita J2. The compounds acetic acid, isovaleric acid, octanoic acid and ethyl octanoate had an average lethal concentration (LC50) of 192, 95, 236.08, 134.30, 226.10, respectively, at J2 of M. incognita. In an in vitro test, these molecules significantly reduced (P <0.01) the outbreak of J2 of M. incognita, with greater efficiency for the compounds ethyl octanoate and acetic acid, which caused a reduction of 88.7% and 84.7%, respectively, in negative control. These two compounds, when applied to the substrate infested with M. incognita eggs, reduced infectivity by 95.68 and 93.24% and reproduction by 99.34 e 92.73% compared to the negative control. The application of ethyl octanoate caused a reduction in the number of eggs to values similar (P <0.05) to the positive control (Basamid). The molecules ethyl octanoate and acetic acid showed good prospects as candidates for nematicides for agribusiness after further research.